Factors related to parenting stress among fathers of preschool children in Japan. Issue 1 (12th April 2022) - Kachi, Yuko; Ochi, Manami; Kato, Tsuguhiko; Otsuka, Miyako; Takehara, Kenji
Abstract: Background: Even though fathers participate in childcare at a higher rate than before, there remains a lack of research on the factors that contribute to parenting stress among fathers. This study explored the socioeconomic and demographic factors associated with parenting stress among fathers of preschool children. Methods: Our study included 17 645 fathers who participated in the 2016 Comprehensive Survey of Living Conditions in Japan. Parenting stress was assessed using a single question. Socioeconomic and demographic factors were predictors. Logistic regression analysis was conducted to estimate the odds ratio (OR) and 95% confidence interval (CI) for parenting stress. Results: Overall, 6.6% fathers experienced parenting stress. Fathers with a youngest child aged 0–2 years were more likely to experience parenting stress than those with a youngest child aged 3–6 (OR: 1.45, 95% CI: 1.25–1.68). Compared with fathers who lived in two‐parent households without grandparents, those who lived in single‐father households (both with and without grandparents) were more likely to experience parenting stress (OR: 12.13, 95% CI: 5.60–26.29 and OR: 4.19, 95% CI: 2.04–8.60, respectively). Furthermore, there was a significant negative association between education and parenting stress. Conclusions: Having a child aged 0–2 years, single fatherhood, and higher education were associated with parenting stress among fathers of preschool children. Healthcare professionals need to be aware of these factors when supporting fathers in raising their children.